Institutionalization of Delegated Legislation in Ukraine as a Requirement of European Integration - Katylov, Vladyslav (Problems of legality, 2026)
The article provides a comprehensive theoretical and legal study of the institute of delegated legislation in the context of adapting the Ukrainian legal system to European Union standards. The relevance of the topic is driven by the need to find a balance between the efficiency of the executive branch and the preservation of the rule of law principle within the framework of European integration processes. The aim of the article is to substantiate the necessity of legislative consolidation of the mechanism for delegating legislative powers in Ukraine and to define the conceptual foundations of its functioning in accordance with the principles of good governance. The methodological basis of the study comprises a complex of general scientific and special legal methods. The comparative method was used to analyze models of delegated legislation in EU countries (France, Germany, the United Kingdom); the historical-legal method was applied for a retrospective analysis of national experience; the systemic-structural method allowed for determining the place of delegated acts within the hierarchy of legal sources. The study analyzes the historical retrospective of this institute's development in Ukraine, starting from the state-building processes of 1918–1920, through the Soviet period of "quasi-delegation," to the controversial experience of the Cabinet of Ministers of Ukraine issuing decrees in the early 1990s. Particular attention is paid to the modern doctrine of the Constitutional Court of Ukraine, which defined the fundamental criteria for the legality of transferring legislative powers: legality, reasonableness, subsidiarity, and mandatory control by the delegating entity. A comparative analysis was conducted on the models of delegated legislation in leading European countries (the UK, France, Germany) and the legal nature of delegated acts of the European Commission in accordance with Article 290 of the Treaty on the Functioning of the European Union (TFEU). The necessity of transitioning from fragmented sub-legislative rule-making to the systemic institutionalization of delegated legislation is substantiated. The author proves that the lack of specific legislative regulation creates risks for legal certainty and may hinder the implementation of the acquis communautaire. As a result of the study, the author proposes a concept for a future Law of Ukraine "On Delegated Legislation," which should clearly distinguish between executive rule-making and legislative delegation, introduce a mechanism for "Enabling Acts," and establish a multi-level system of parliamentary and judicial oversight.